2020
DOI: 10.35759/jabs.151.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation du potentiel antimicrobien et de la toxicité des extraits de Jatropha multifida Linn, (Euphorbiaceae)

Abstract: Objectif : L’objectif de ce travail était d’évaluer in vitro l’activité antimicrobienne des extraits de feuilles et tige de Jatropha multifida sur la croissance de Candida albicans, Escherichia coli et Staphylococcus aureus, puis d’évaluer in vivo la toxicité de cette plante. Méthodologie et résultats : Les méthodes de diffusion en milieu gélosé et de microdilution en milieu liquide ont été utilisées pour évaluer l’effet antimicrobien. Une étude en subaigüe était réalisée afin d’explorer les effets toxiques de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For instance, Sheeba et al , [ 33 ] and Mondal and Suresh [ 34 ] have previously reported that flavonoids and tannins were present in Cleome rutidosperma ’ roots and Cassia occidentalisa leaves, and they observed healing of experimentally induced wounds in rats. Besides, the antioxidant and antimicrobial activities of flavonoids contained in the sap extract of J. multifida (Linn) have also been reported [ 23 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Sheeba et al , [ 33 ] and Mondal and Suresh [ 34 ] have previously reported that flavonoids and tannins were present in Cleome rutidosperma ’ roots and Cassia occidentalisa leaves, and they observed healing of experimentally induced wounds in rats. Besides, the antioxidant and antimicrobial activities of flavonoids contained in the sap extract of J. multifida (Linn) have also been reported [ 23 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…J. multifida (Linn) is known over the years as one of the medicinal plants whose sap extract has been widely used for wound healing in Benin. Agban et al [23] and Aiyelaagbe et al [24], have previously reported the antibacterial effect of the leaves, stems, and roots extract of Jatropha multifida Linn. Indeed, E. guineensis (kernel oil) extract has been used over the years in Nigeria in the treatment and management of various skin diseases and infections in both humans and animals [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation